TEOLOGI PEMBEBASAN PEREMPUAN DALAM ISLAM - Luthfi Maulana (MUWAZAH : jurnal kajian gender, 2015)
This study aims to understand the theology of liberation as an alternative solution that freed because of the discrimination against women. Discrimination against women is a result of the hegemony of patriarchal society jahiliya that is still growing in the view of Islam, so that religion can not function as a mercy to entire human race. Religion as the foundation of justice also become invisible. That condition requires a liberating theology, so it can be used as an alternative to achieve maslaha of the people, including women